Estimating Remaining Life and Fitness-For-Services Evaluation of Fuel Piping Systems - Purwidyasari, Sekar Putri; Kurniawan, Ahmad Isni; Ferdian, Deni (Journal of Materials Exploration and Findings, 2023)
Assets life extension are required to predict the design life expiry based on condition and effects of deterioration. The remaining life assessment will answer the questions about timing of the component or equipment will lead to failure and shall be evaluated by inspection and maintenance monitoring. This study elaborates process calculation and analysis by using remaining life assessment and fitness for services method according to API 579-1/ASME FFS-1 for process piping area. The result of remaining useful life estimation and estimated life has been proposed. There are 11 piping systems based on the condition monitoring with thickness measurements. The result is 2 piping systems was not reached more than 20 years of age and continue to the assessment of fitness for service. The result for Inlet Naphtha 946-TK-5 piping systems is accepted for assessment level 1, both the result of evaluating average measured criteria and evaluating minimum measured thickness. The piping systems can continue the operation until the estimated life. Another result for Discharge Crude 946-P1AB to CDU piping systems was not accepted due to the minimum measured thickness not met the criteria. Hence, the piping systems is potentially unsafe with the given data during the lifetime.